2020
DOI: 10.1002/col.22566
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing a decade of Colors of the Year

Abstract: The Color of the Year was first introduced by Pantone in 2000, and recently (the last decade) we saw the trend of introducing a Color of the Year being picked up by more and more companies. Paints and coatings companies typically select their colors of the year by extensive research by designers and trend experts, resulting in a plurality of colors being introduced as Color of the Year,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Art paintings are considered to purely reflect the artist’s taste or preference for colours. Essentially, the work is an expression of the artist’s personal aesthetic experience, and diversity is naturally expected, although there are non-personal trends for various styles and articulations that are influenced by social or environmental factors 4 , 5 . Despite the highly personal nature of art paintings, often linked to the notion that ‘ beauty is in the eyes of the beholder ’, there exist art paintings in which different individuals find similar aesthetic pleasure.…”
Section: Introductionmentioning
confidence: 99%
“…Art paintings are considered to purely reflect the artist’s taste or preference for colours. Essentially, the work is an expression of the artist’s personal aesthetic experience, and diversity is naturally expected, although there are non-personal trends for various styles and articulations that are influenced by social or environmental factors 4 , 5 . Despite the highly personal nature of art paintings, often linked to the notion that ‘ beauty is in the eyes of the beholder ’, there exist art paintings in which different individuals find similar aesthetic pleasure.…”
Section: Introductionmentioning
confidence: 99%
“…Our study could also have practical implications for the fashion and marketing communication industries. While the Pantone Color of the Year leads the fashion trend and suggests a relatively fragmented and intensive variation in color trends, 61 our findings show that people's perceptions of basic colors were relatively stable over the last 200 years. Marketing and fashion companies could consider color‐emotion patterns when planning their marketing campaign strategies for the cyclic attention of color stories.…”
Section: Discussionmentioning
confidence: 57%
“…Meanwhile, if designers can have a design guideline to follow and a reliable database based on big data information of the product to use, it will be better for them to achieve near optimal color design for certain product 3 . Gijsenij et al scholars analyzed the color of the year for paint companies over the past decade and found that analyzing the trends of the color of the year rather than a single color would provide greater help in color design 4 . In order to establish an objective and effective color trends prediction system, researchers have attempted to employ quantitative methods based on past qualitative studies so that explore the trend of popular colors with the help of mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…3 Gijsenij et al scholars analyzed the color of the year for paint companies over the past decade and found that analyzing the trends of the color of the year rather than a single color would provide greater help in color design. 4 In order to establish an objective and effective color trends prediction system, researchers have attempted to employ quantitative methods based on past qualitative studies so that explore the trend of popular colors with the help of mathematical models. Many research methods and theories have started to be applied to this field by researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation